Management in transitional economies : from the Berlin Wall to the Great Wall of China - Malcolm Warner; Warner, Malcolm (London ; New York : Routledge, Taylor & Francis Group, 2017)
"This book examines the past, present and future of management in the transitional economies of East and Central Europe, Russia, the People's Republic of China, and the Socialist Republic of Vietnam. It discusses the nature of the transition process, identifies different transitional paths, highlights common features and outlines a number of theoretical approaches. Each chapter covers a wide range of management issues in the countries covered, including the details of the country's historical and cultural background, the transition process, external and internal factors, and its macro- and micro-economic contexts. This work should be of interest to both an academic, as well as a practitioner, readership, across a wide range of disciplines."--Jacket.
From plan to market -- Central Europe 1 : successful transformation -- Central Europe 2 : "Valleys of Tears" -- Russia : the hard road from perestroika -- China : "crossing the river by feeling the stones" -- Vietnam : a pragmatic hybrid model -- Processes and outcomes.
Includes bibliographical references (pages 185-200) and index.
Rasal
Keywords: economies -- Europe, Central; Management -- Russia (Federation); China; Europe, Central; Russia (Federation); Vietnam